PTH-049 Single port laparoscopic colectomies for ibd in an elective and emergency setting; the new gold standard?. (22nd June 2015) - Ainley, P; Shaban, F; Borowski, D; Garg, D; Gill, T
Abstract : Introduction: Single-port laparoscopic surgery is becoming more prevalent worldwide. Our colorectal unit is leading in UK practice in performing single-port surgery (SILS). We present our case series on elective and emergency laparoscopic total colectomies and proctocolectomies for IBD. Our aim is to compare outcomes of SILS vs. multi-port surgery. Method: A retrospective study of all laparoscopic total colectomies and proctocolectomies performed in our unit for IBD between May 2009 and Dec 2014 by two Colorectal Surgeons was conducted. We collected data on emergency vs. elective, single vs. multi-port, operation time, LOS, resumption of diet, time to stoma output and complications. Results: 35 cases in total were performed: 19 SILS, 14 multi-port, 1 SILS assisted, 1 multi-port assisted. There were 16 emergency cases and 19 elective. Average operative time was shorter in SILS (253 vs. 301 min). Average LOS was shorter in the SILS group (6.95 vs. 10 days). Average days to resumption of diet was shorter in the SILS group (2.00 vs. 2.80 days). Average time to stoma output was similar (2.38 days in SILS and 2.36 in Multi-port). 30-day complication rate was lower in the SILS group (15.8% vs 42.9%); there were 2 returns to theatre in the SILS group vs. 1 in the multi-port. Conclusion: In our experience single port laparoscopic colectomies are a superior alternative to the traditional multi-port approach. Our figures show that it has a shorter operating time, shorter length of stay, quicker resumption of diet and a lower complication rate and we recommend that it should become the new gold standard. Disclosure of interest: None Declared.